2003
DOI: 10.1002/pmic.200300399
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for the comparative analysis of serum proteomes for the discovery of biomarkers for hepatocellular carcinoma

Abstract: Many of the emerging technologies for the global evaluation of gene expression, at both the RNA and protein level, are being applied to the problem of finding biomarkers for human disease progression. These analyses can be made difficult, however, by variation between samples that arises from both technical and nondisease related physiological or genetic causes. In an effort to identify serum polypeptides whose presence or absence correlates with the clinical status of patients at high risk for hepatocellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(89 citation statements)
references
References 31 publications
10
74
1
1
Order By: Relevance
“…Interestingly, some of the identified biomarkers in our study were found to be modulated by various cancer diseases in other serum-based proteomic studies. Thus, haptoglobin was found upregulated in serum of ovarian, oesophageal and small-cell lung cancer patients (Steel et al, 2003;Ahmed et al, 2004;Bharti et al, 2004), while complement C3 and apolipoprotein A1 (Steel et al, 2003;Zhang et al, 2004) were found downmodulated in liver or ovarian cancer. However, these studies were dedicated to the identification of serum biomarkers associated to cancer diagnosis, rather than prediction of clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some of the identified biomarkers in our study were found to be modulated by various cancer diseases in other serum-based proteomic studies. Thus, haptoglobin was found upregulated in serum of ovarian, oesophageal and small-cell lung cancer patients (Steel et al, 2003;Ahmed et al, 2004;Bharti et al, 2004), while complement C3 and apolipoprotein A1 (Steel et al, 2003;Zhang et al, 2004) were found downmodulated in liver or ovarian cancer. However, these studies were dedicated to the identification of serum biomarkers associated to cancer diagnosis, rather than prediction of clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of many efforts to overcome this broad dynamic range problem, most proteomic biomarker discovery studies have nevertheless described relatively abundant host response proteins as candidate biomarkers. 3,4 The host response comprises a cascade of inflammatory signals that can be triggered by very small inciting events, e.g., a localized infection or a small tumor, and that leads to up-and downregulation of a group of circulating proteins often called acute phase reactants. [5][6][7] These proteins are mostly synthesized by the liver and include albumin, transthyretin, retinol binding proteins, clotting proteins, lipoproteins, c-reactive protein and immune mediators, among others.…”
mentioning
confidence: 99%
“…Many protein cleavage fragments, including the N-terminal end of glypican-3 (Hippo et al, 2004), the C-terminal end of vitronectin (Paradis et al, 2005), a fragment of complement C3 (Steel et al, 2003) and the N-terminal ends of calreticulin and of PDIA3 (Chignard and Beretta, 2004), have been reported to be specific to HCC. Also reported in HCC were specific isoforms of apolipoprotein A1 (Steel et al, 2003;Fernandez-Irigoyen et al, 2005), variants of aldehyde dehydrogenase isozymes (Park et al, 2002a) and hyperfucosylation of Golgi Protein 73 (Block et al, 2005). It is estimated that there are more than 100 different post-translational modifications (e.g., glycosylation, phosphorylation, oxidation) (Krishna and Wold, 1988;Yang, 2005), although only a few have yet been studied in HCC.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%